Upaya Kepala sekolah dalam Peningkatan Kinerja Guru di SD GMIT 024 Likwatang - Nehemia Fanpada; Elia Fantang; Desi Centrin Mautang (Jurnal Ilmiah Wahana Pendidikan, 2023)
Teacher performance is an achievement that is achieved as the ability of a teacher who has been demonstrated in carrying out duties and responsibilities in certain fields, especially in schools while carrying out learning activities whose impact can provide encouragement and influence on students so that learning objectives can be achieved and run well and as expected, which is shown in appearance, actions, and work performance. The method used in this research is descriptive method with a quantitative approach which aims to describe the conditions that occur in the field using numbers in percent. The research results obtained are the efforts that have been made by the leadership as an effort to improve teacher performance.